Optimization of planting date and irrigation strategy for sustainable cotton production - Fan, Hongjian; Xue, Lu; Ma, Hao (Frontiers in Sustainable Food Systems, 2024)
Introduction The study aims to evaluate the impact of climatological factors on rice yield and methane emissions in Southern Shaanxi’s rice cultivation areas, with the goal of informing effective Climate-Smart Agriculture (CSA) strategies. Methods A three-year longitudinal analysis (2017-2019) was conducted, examining the correlation between rice productivity and weather conditions within the agricultural ecosystem. Data on rice yields and methane emissions were collected and analyzed to determine patterns and trends. Results Significant correlations were identified between rice yield and weather conditions, with favorable weather for rice growth correlating with higher methane emissions. Methane emissions were particularly high during the vegetative and reproductive stages of rice growth, peaking 60 to 90 days after transplanting. Average emissions for this period were 245.2±80.1 kg CH4 ha-1 in 2017, 274.2±93.9 kg CH4 ha-1 in 2018, and 339.6±50.3 kg CH4 ha-1 in 2019. Total cumulative methane emissions over the entire rice cultivation period were 635.0±177.2 kg CH4 ha-1 in 2017, 661.2±239.2 kg CH4 ha-1 in 2018, and 679.4±205.4 kg CH4 ha-1 in 2019, with no statistically significant interannual differences. Discussion The findings highlight the need to balance the goals of reducing greenhouse gas emissions for climate change mitigation with the enhancement of rice yield within CSA practices. The organic link between rice productivity and methane emissions under varying weather conditions suggests that an integrated approach to CSA is essential, considering climate adaptability, productivity, and greenhouse gas reduction. The study’s results contribute to a deeper scientific understanding of local agricultural ecosystems and provide a basis for developing management techniques for CSA. Conclusion An integrated approach to CSA that takes into account the interplay between rice yield, methane emissions, and climatological factors is crucial for achieving sustainable agricultural practices in Southern Shaanxi. The study’s insights can guide the development of strategies that enhance both rice productivity and environmental sustainability.